Community Readiness In The Development Of Marine Tourism In Tanjung Setia Village, Pesisir Barat, Lampung - Melati Fitra Aziza Melati; Endah Triwahyuningtyas Endah; Renalmon Hutahaehan Renalmon (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2023)
Indonesia has been well-known US a country with abundant natural resources potential, especially in the maritime field. One of the areas in which has nautical tourism assets in Indonesia is Lampung. The nautical tourism asset in Lampung is located in Krui , West Coast Regency. The beach is called Tanjung Setia. The main attraction possess by this beach is Surfing. The wave characteristic of Tanjung Setia Beach is long, high, and constant. With its assets, the reality isn't in accordance with the readiness of the society living along the Beach yet. It is found that the community in Tanjung Setia haven't realized yet, proved by there is no programs nor ideas given to the developing of the tourism by the POKDARWIS – a group created to develop the tourism awareness in Tanjung Setia. Besides, they are also not able yet to catch the opportunity given by the tourism in their village. According to Nur Nobi and Majumder (2009:1-2) it is said that developing a tourism (nautical tourism) is including some important factors, in which one of them is the involvement of the society. Methodology used in this study is descriptive with qualitative approach. The grand theory used in this study is the stage of community readiness consists of 9 levels, they are: unawareness, declining, vivid awareness, pre- plan, preparation, initiation, stability, confirmation, and professionalism . The next step, this study will be testing at the level in which the community of Tanjung Setia is on, then analyzed by frequency distribution. In this study, it was found that, the majority of Tanjung Setia village community are farmers, with the average age is 36-42 years. Public facilities in the Tanjung Setia the beach area is quite good, but there are still many things that need to be developed. In terms of readiness, the people of Tanjung Setia village occupy level 5 of 9. They are in the preparation stage, where at this level the community of Tanjung Setia village is ready to develop marine tourism in their village